Crosslinked copolymer, polymer membrane containing same, and anion exchange membrane containing said polymer membrane

JP2025505117AActive Publication Date: 2025-02-21HANWHA SOLUTIONS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024543237
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-02-02
Filing Date
2023-02-03
Publication Date
2025-02-21
Estimated Expiration
2043-02-03

AI Technical Summary

Benefits of technology

【0018】 本発明の架橋共重合体は、高い含水率(water uptake、WU)を有しながらも寸法安定性に優れ、イオン伝導度、水和度、およびアルカリ安定性が高い。また、前記架橋共重合体は、引張強度と伸び率特性などの機械的物性が非常に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505117000001_ABST
    Figure 2025505117000001_ABST
Patent Text Reader

Abstract

The present invention provides a new crosslinked copolymer which has excellent mechanical properties, excellent stability against hydroxide ions, high ionic conductivity and degree of hydration, and can be preferably used as an anion exchange membrane (AEM) material for fuel cells and the like.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0014254 filed on February 3, 2022 and Korean Patent Application No. 10-2023-0014346 filed on February 2, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a cross-linked copolymer, a polymer membrane containing the same, and an anion exchange membrane containing the polymer membrane. [Background technology]

[0003] Anion exchange membrane fuel cells (AEMFCs) have been continuously improved, especially in terms of power density, and are becoming more price competitive as non-PGM catalysts are applied. Due to these advantages, AEMFCs have attracted much attention as an alternative to proton exchange membrane fuel cells (PEMFCs) that use expensive PGM-based catalysts and perfluorinated polymers such as Nafion. However, for such AEMFCs to be commercialized, further improvements in cell durability and power density are required. Therefore, the performance of the AEM (anion exchange membrane), which has a significant impact on the overall performance of AEMFCs, must be improved to the desired level. To achieve this, it is necessary to develop a new AEM that is physicochemically stable under the actual operating conditions of AEMFCs (i.e., high pH, ​​temperature, and RH conditions) while also improving ionic conductivity.

[0004] AEMs generally consist of a polymer backbone, i.e., a hydrophobic component that governs the overall membrane properties, and an ion-conducting head group, i.e., a hydroxide ion (OH - ) and hydrophilic components involved in the transfer of charge. Therefore, the conductive headgroup and polymer backbone must be studied simultaneously to improve the overall performance of AEMs.

[0005] Among the ion-conducting head groups, piperidinium, pyrrolidinium, substituted imidazolium, and cyclic ammonium derivatives such as 6-azonia-spiro[5,5]undecane are the subject of frequent investigation due to their high stability. Quaternary ammonium groups, especially hexyltrimethylammonium, are widely used due to their chemical stability almost equal to that of the cyclic ammonium derivatives.

[0006] Meanwhile, various polymer backbones such as poly(phenylene oxide) (PPO), poly(ether ketone) (PEK), poly(ether sulfone) (PES), polybenzimidazole (PBI), poly(phenylene) (PP), polyolefin, spirobisindene and polynorbornene (NB) have been studied. There have also been various attempts to improve the performance of AEMs by employing various strategies based on multiblock copolymers, fluoropolymers, spacer-type polymers, multi-cation systems and cross-linked polymers. However, despite all these efforts, only a few of such AEMs exhibit performance similar to PEMs. These AEMs were characterized by having piperidinium or hexyltrimethylammonium as ion-conducting head groups and polycarbazole, polybiphenyl, polyterphenyl or polybibenzyl as aromatic polymer backbones. Unlike PPO or PES, these polymers are based on a backbone without aryl ether linkages, ensuring excellent chemical stability towards hydroxide ions, as well as the ion-conducting headgroups being incorporated within or grafted to the backbone structure, providing high ion exchange capacity (IEC), conductivity, and overall cell performance.

[0007] However, such rigid aromatic polymers generally have low water absorption rates. In ion-conducting polymers such as AEM and PEM, water tends to act as a medium for ion conduction, and therefore high ionic conductivity can only be achieved at a certain level of water content (WU). In a previous study, AEM based on such rigid aromatic polymers was found to have a water absorption rate of 2.5 meq g -1 or higher (i.e., by introducing more ion-conducting groups), thus providing the required level of WU and ionic conductivity. However, the positively charged ion-conducting head groups are relatively less stable to hydroxide ions compared to the polymer backbone, which means that the introduction of more ion-conducting groups may have a negative effect on the stability of the AEM.

[0008] Furthermore, such AEMs are mechanically robust but have relatively poor elastic properties. The mechanical properties of the AEMs can actually mean membrane destruction during cell operation (e.g., pinhole formation or failure at the periphery of the membrane electrode assembly (MEA) active area), so achieving a certain level of elongation is preferred to ensure high performance of AEMFCS.

[0009] Poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS) is a polymer that exhibits phase separation of styrene and butylene as block structures, and has excellent elastic properties and chemical stability. There have been various attempts to utilize SEBS as an AEM by introducing ion-conducting head groups, and some of these efforts have resulted in the development of AEMs with excellent phase separation and high ionic conductivity, despite their relatively low IEC values.

[0010] At the same time, such SEBS-based AEMs have very low tensile strength and high swelling ratio (SR). These mechanical properties make it more difficult to process SEBS into thin membranes and can cause excessive swelling under humid conditions, i.e., the actual operating conditions of fuel cells. In addition, such SEBS polymers have very limited solubility. Therefore, it is very difficult to adjust the functionalization degree of SEBS or to mix or graft it with other molecules having desired properties to improve the conductivity or mechanical properties of the AEMs. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Korean Patent No. 10-1535062 [Non-patent literature]

[0012] [Non-Patent Document 1] Nat. Energy 4 (2019) 392-398 [Non-Patent Document 2] Nat. Commun. 12 (2021) 2367 [Non-Patent Document 3] Adv. Funct. Mater. 28 (2018) 1-10 [Non-Patent Document 4] Int. J. Hydrogen Energy 46 (2021) 18524-18533 [Non-Patent Document 5] J. Mater. Chem. A. 9 (2021) 327-337 [Non-Patent Document 6] J. Membr. Sci. 642 (2022), 119966 [Non-Patent Document 7] ACS Macro Lett. 6 (2017) 566-570 [Non-Patent Document 8] Energy Environ. Sci. 13 (2020) 3633-3645

Non-licensed literature 9

Non-licensed literature 10

Non-licensed Document 11

Non-licensed Document 12

Non-licensed Document 13

Non-licensed Document 14

Non-licensed Document 15

Non-licensed Document 16

Non-licensed Document 17

Non-licensed Document 18

Non-licensed Document 19

Non-licensed Document 20

Non-licensed Document 21

Non-licensed Document 22

[0013] The present invention aims to provide a new crosslinked copolymer which has excellent mechanical properties, excellent stability against hydroxide ions, high ionic conductivity and degree of hydration, and can be preferably used as an anion exchange membrane (AEM) material for fuel cells and the like. [Means for solving the problem]

[0014] Therefore, according to one embodiment of the present invention, there is provided a cross-linked copolymer comprising a first chain represented by the following formula 1 and a second chain represented by the following formula 2, wherein the first chain and the second chain are cross-linked to each other:

[0015] [ka] In the above Chemical Formula 1, * indicates the bonding position with Chemical Formula 2, The sum of q1, q2, q5, and q6 is an integer from 100 to 1,000; The sum of q3 and q4 is an integer from 150 to 2,000, a and b are each independently an integer of 3 to 10; R1 to R4 are each independently hydrogen or -(CH2) p -CH3, and p is an integer from 0 to 5; [ka] In the above Chemical Formula 2, * indicates the position of binding to Chemical Formula 1, R5 is -(CH2) p’ -CH3, and p' is an integer from 0 to 5, n is an integer from 10 to 1,000.

[0016] According to an embodiment of the present invention, there is provided a polymer membrane comprising the cross-linked copolymer.

[0017] According to one embodiment of the present invention, (a) preparing a poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer represented by the following chemical formula 1-1; (b) preparing a poly(m-terphenyl N-alkylpiperidine) polymer represented by the following formula 2-1: (c) crosslinking the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer with the poly(m-terphenyl N-alkylpiperidine) polymer to prepare a crosslinked copolymer; A method for producing a crosslinked copolymer is provided, comprising: [ka] In the above Chemical Formula 1-1, The sum of q1, q2, q5, and q6 is an integer from 100 to 1,000; The sum of q3 and q4 is an integer from 150 to 2,000, a and b are each independently an integer of 3 to 10; R1 to R4 are each independently hydrogen or -(CH2) p -CH3, and p is an integer from 0 to 5; X1 and X2 are each independently a halogen group; [ka] In the above Chemical Formula 2-1, R5 is -(CH2) p’-CH3, and p' is an integer from 0 to 5, n is an integer from 10 to 1,000. Effect of the Invention

[0018] The crosslinked copolymer of the present invention has excellent dimensional stability, high ionic conductivity, degree of hydration, and alkali stability while having a high water uptake (WU), and also has excellent mechanical properties such as tensile strength and elongation.

[0019] As described above, the crosslinked copolymer of the present invention has excellent electrochemical properties and mechanical properties, and therefore can be suitably used as a material for anion exchange membranes. [Brief description of the drawings]

[0020] [Figure 1] 1 shows the structure of a poly(m-terphenyl-N-methylpiperidinium)-SEBS membrane 1 (x-PmTP-SEBS) according to one embodiment of the present invention. [Diagram 2] FIG. 13 shows (a) hydration number (λ) vs. IEC and (b) mechanical properties of x-PmTP-SEBS (stars) compared to OH-form SEBS-based AEMs (circles) and poly(phenylene)-based AEMs (squares) reported in the literature at room temperature. [Diagram 3] (ac) SEM surfaces and (df) AFM images of PmTP-SEBS membranes: (a and d) 30x-PmTP-SEBS, (b and e) 40xPmTP-SEBS and (c and f) 50xPmTP-SEBS membranes. [Figure 4] 1 is a graph showing the SAXS profile of an x-PmTP-SEBS membrane. [Diagram 5] 1 shows (a) a TGA graph of x-PmTP-SEBS membrane from 30° C. to 300° C. and (b) a graph showing the relative ratio of free water to bound water in x-PmTP-SEBS membrane. [Figure 6]FIG. 1 shows a graph comparing (a) ionic conductivity (solid line) and normalized conductivity (dotted line) and (b) normalized conductivity of x-PmTP-SEBS membranes compared to representative membranes from the literature. [Figure 7] 1 is a graph showing (a) hydroxide ion conductivity and (b) residual IEC of x-PmTP-SEBS membranes at 80° C. in 2 M KOH. [Figure 8] Graph showing single cell performance of x-PmTP-SEBS membrane with (a) no back pressure and (b) 0.1 MPa back pressure. [Figure 9] 1 is a graph showing the 1H NMR spectrum of poly(m-terphenyl-N-piperidine) 2. [Figure 10] 1 is a graph showing 1H NMR spectra of (a) SEBS, (b) bromohexanoyl SEBS4, ​​and (c) bromohexyl SEBS3. [Figure 11] FTIR spectra of bromohexanoyl SEBS4 and its derived form, bromohexyl SEBS3. [Figure 12] 1 is a photograph of cross-linked (m-terphenyl-N-methylpiperidinium)-SEBS membranes (x-PmTP-SEBS) with different cross-linking degrees. [Figure 13] FTIR spectra of x-PmTP-SEBS membranes with different crosslinking degrees. [Figure 14] 1 is a graph showing the mechanical properties of x-PmTP-SEBS AEM at 50% RH condition. [Figure 15] 1 shows (a) TGA and differential thermal analysis (DTG) graphs and (b) differential scanning calorimetry (DSC) graph of x-PmTP-SEBS membrane. [Figure 16] Graphs showing DSC plots of x-PmTP-SEBS membranes at (a) -40°C to 20°C and (b) -10°C to 0°C. [Figure 17] 1 is a graph comparing the maximum power density of PP-based and SEBS-based AEMFCs with x-PmTP-SEBS membranes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0022] It is to be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, steps, components, or combinations thereof, but do not preclude the possible presence or addition of one or more other features, steps, components, or combinations thereof.

[0023] Although the present invention can be modified in various ways and has various forms, specific embodiments are exemplified and described in detail below. However, it is not intended to limit the present invention to the specific disclosed embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.

[0024] The present invention will be described in detail below. According to one embodiment of the present invention, there is provided a cross-linked copolymer comprising a first chain represented by the following formula 1 and a second chain represented by the following formula 2, wherein the first chain and the second chain are cross-linked to each other. [ka] In the above Chemical Formula 1, * indicates the bonding position with Chemical Formula 2, The sum of q1, q2, q5, and q6 is an integer from 100 to 1,000; The sum of q3 and q4 is an integer from 150 to 2,000, a and b are each independently an integer of 3 to 10; R1 to R4 are each independently hydrogen or -(CH2) p -CH3, and p is an integer from 0 to 5; [ka] In the above Chemical Formula 2, * indicates the position of binding to Chemical Formula 1, R5 is -(CH2) p’ -CH3, and p' is an integer from 0 to 5, n is an integer from 10 to 1,000.

[0025] The crosslinked copolymer of the present invention is formed by crosslinking a first chain containing poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS) with a second chain containing poly(m-terphenyl N-alkyl piperidine) (PmTP).

[0026] By satisfying this structure, the cross-linked copolymer exhibits higher tensile strength and Young's modulus than existing SEBS-based cross-linked copolymers, and exhibits significantly improved elongation properties compared to PP-based polymers. In addition, the cross-linked copolymer exhibits high water retention capacity and high hydration number due to the free volume induced by the twisted structure of m-terphenyl, thereby exhibiting high ionic conductivity. In addition, the cross-linked copolymer has excellent alkali stability and exhibits a shielding effect due to its high hydration number. Therefore, the cross-linked copolymer can be suitably used as an anion exchange membrane for fuel cells, etc.

[0027] The ratio of the first chain represented by Chemical Formula 1 and the second chain represented by Chemical Formula 2 can be adjusted according to the desired physical properties. As an example, the crosslinked copolymer may contain 10 moles or more, or 20 moles or more, or 30 moles or more, or 40 moles or more, and 70 moles or less, or 60 moles or less, or 50 moles or less of the second chain per 100 moles of the first chain. When the ratio of the first chain and the second chain of the crosslinked copolymer satisfies the above range, it can exhibit excellent mechanical properties and electrochemical properties.

[0028] Preferably, the sum of q1, q2, q5, and q6 may be an integer of 100 or more, or 150 or more, or 200 or more, or 250 or more, or 300 or more, or 350 or more, or 400 or more, or 450 or more, or 500 or more, and 1,000 or less, or 950 or less, or 900 or less, or 850 or less, or 800 or less.

[0029] Preferably, the sum of q3 and q4 may be an integer of 150 or more, or 200 or more, or 250 or more, or 300 or more, or 350 or more, or 400 or more, or 450 or more, or 500 or more, or 550 or more, or 600 or more, and 2,000 or less, or 1,800 or less, or 1,600 or less, or 1,500 or less, or 1,400 or less, or 1,200 or less, or 1,000 or less.

[0030] Preferably, q1 to q6 may each independently be an integer of 10 or more, or 20 or more, or 25 or more, or 30 or more, and 500 or less, or 450 or less, or 400 or less, or 350 or less, or 300 or less.

[0031] Preferably, the ratio of the sum of q1, q2, q5, and q6 to the sum of q1 to q6, i.e., the total molar fraction of styrene-derived repeating units to all repeating units of Chemical Formula 1, may be 0.2 or more, or 0.25 or more, or 0.3 or more, and 0.5 or less, or 0.45 or less.

[0032] Preferably, the ratio of the sum of q1 and q6 to the sum of q1, q2, q5, and q6, i.e., the total molar fraction of unsubstituted styrene repeat units to all styrene-derived repeat units in Chemical Formula 1, may be 0.2 or more, or 0.25 or more, or 0.3 or more, or 0.35 or more, and 0.5 or less, or 0.45 or less, or 0.4 or less.

[0033] Preferably, n is an integer of 10 or more, or 100 or more, or 150 or more, and 1000 or less, or 500 or less.

[0034] Preferably, a and b may each independently be an integer of 3 or more, or 4 or more, and 10 or less, or 9 or less, or 8 or less, or 7 or less, or 6 or less.

[0035] Preferably, R1 to R4 are each independently hydrogen or -(CH2) x -CH3, where x may be an integer of 0 to 3, or an integer of 0 to 2. Preferably, R1 to R4 may all be hydrogen.

[0036] Specifically, the crosslinked copolymer may include a repeating unit represented by the following formula 3: [ka] In Chemical Formula 3, q1 to q6, a, b, and n are as defined in Chemical Formula 1 and Chemical Formula 2.

[0037] Preferably, the crosslinked copolymer may include a repeating unit represented by the following formula 4: [ka] In Chemical Formula 4, q1 to q6 and n are as defined in Chemical Formula 1 and Chemical Formula 2.

[0038] Figure 1 shows the crosslinked structure of compound (1) represented by formula 4 according to one embodiment of the present invention. As shown on the right side of Figure 1, the crosslinked copolymer of the present invention has a structure in which a poly(styrene-b-ethylene-co-butylene-b-styrene) polymer and a poly(m-terphenyl N-alkylpiperidine) polymer are crosslinked with each other. Due to such structural characteristics, the crosslinked copolymer exhibits high tensile strength and elongation, and has a high water retention capacity and hydration number, thereby exhibiting excellent ionic conductivity and cell performance.

[0039] The above-mentioned crosslinked copolymer has a positively charged quaternary ammonium group, and can selectively pass only anions. Therefore, the crosslinked copolymer can be used as an anion exchange membrane. The counter ion (anion) group for the cation (quaternary ammonium group) of the crosslinked copolymer is OH. - , Cl - , Br - , or HCO3 - and preferably, OH - may be also possible.

[0040] Therefore, according to one embodiment of the present invention, there is provided a polymer membrane comprising the cross-linked copolymer.

[0041] The polymer membrane containing the cross-linked copolymer may have a thickness of 20 μm or more, or 30 μm or more, or 45 μm or more, or 55 μm or more, and 70 μm or less, or 60 μm or less, or 55 μm or less. When the thickness of the polymer membrane satisfies the above range, it exhibits high mechanical properties and is also excellent in electrochemical properties, making it suitable for use as an anion exchange membrane.

[0042] The above-mentioned polymer membrane contains a crosslinked copolymer containing the first chain and the second chain, and thus has improved mechanical strength compared to existing polymers for AEM, and exhibits high ionic conductivity while showing an appropriate IEC, and has excellent alkaline stability. Therefore, a polymer membrane having such physical properties can be suitably used as an anion exchange membrane contained in a fuel cell or the like.

[0043] Meanwhile, according to one embodiment of the present invention, there is provided a method for preparing the crosslinked copolymer. Specifically, the method for preparing the crosslinked copolymer of the present invention includes the following steps: (a) preparing a poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer represented by the following chemical formula 1-1; (b) preparing a poly(m-terphenyl N-alkylpiperidine) polymer represented by the following formula 2-1: (c) crosslinking the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer with the poly(m-terphenyl N-alkylpiperidine) polymer to prepare a crosslinked copolymer: [ka] In the above Chemical Formula 1-1, The sum of q1, q2, q5, and q6 is an integer from 100 to 1,000; The sum of q3 and q4 is an integer from 150 to 2,000, a and b are each independently an integer of 3 to 10; R1 to R4 are each independently hydrogen or -(CH2) p -CH3, and p is an integer from 0 to 5; X1 and X2 are each independently a halogen group; [ka] In the above Chemical Formula 2-1, R5 is -(CH2) p’ -CH3, and p' is an integer from 0 to 5, n is an integer from 10 to 100.

[0044] The preferred ranges of q1 to q6, a, b, R1 to R4, and n in the Chemical Formula 1-1 and Chemical Formula 2-1 are as explained in the Chemical Formulas 1 and 2.

[0045] The X1 and X2 are each independently F, Cl, Br, or I, and preferably Br.

[0046] The step (a) is a step of introducing a halogen alkyl group into the styrene portion of the SEBS polymer. Specifically, the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer represented by formula 1-1 can be prepared by Friedel-Crafts acylation of SEBS and reduction of the carbonyl group.

[0047] The acyl halide used in the acylation reaction is selected in consideration of the number of the desired a and b. Specifically, the acyl halide is XR-COCl (X is a halogen and R is C 1-29 In the case where a and b are different from each other or X1 and X2 are different from each other, the acylation reaction can be carried out two or more times using different kinds of acyl halides.

[0048] Aluminum chloride (AlCl3) can be used as a catalyst for the acylation reaction, and the reaction may be carried out at 20 to 30°C for 8 to 24 hours.

[0049] The carbonyl group reduction reaction can be carried out by any method known in the art without any restrictions. For example, triethylsilane and trifluoroacetic acid can be added and reacted at 90 to 120°C for 20 to 30 hours to reduce the carbonyl group. By this reaction, the poly(styrene-b-ethylene-co-butylene-b-styrene) polymer represented by the above formula 1-1 can be obtained.

[0050] The poly(styrene-b-ethylene-co-butylene-b-styrene) copolymer preferably contains 30 moles or more, 40 moles or more, 50 moles or more, 55 moles or more, or 60 moles or more and 90 moles or less, 80 moles or less, 75 moles or less, 70 moles or less, or 65 moles or less of halogen groups per 100 moles of styrene repeating units. The moles of halogen groups per styrene repeating unit can be adjusted by adjusting the moles of acyl halide per moles of styrene in the SEBS polymer during the acylation reaction.

[0051] The step (b) is a step of preparing a poly(m-terphenyl N-alkylpiperidine) polymer. For example, a poly(m-terphenyl N-alkylpiperidine) polymer can be prepared by reacting m-terphenyl with N-alkyl-4-piperidone in the presence of trifluoroacetic acid and trifluoromethanesulfonic acid. For example, the reaction can be carried out at 0 to 10° C. for 12 to 48 hours.

[0052] The step (c) is a step of crosslinking the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer and the poly(m-terphenyl N-alkylpiperidine) polymer to prepare a crosslinked copolymer. The poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer contains a halogen group, and the poly(m-terphenyl N-alkylpiperidine) polymer contains a tertiary amine group, so that the two polymers can be easily crosslinked by a nucleophilic substitution reaction without a separate crosslinking agent.

[0053] In step (c), the poly(m-terphenyl N-alkylpiperidine) polymer is preferably used in an amount of 10 moles or more, or 20 moles or more, or 30 moles or more, or 40 moles or more and 70 moles or less, or 60 moles or less, or 50 moles or less, based on 100 moles of halogen groups contained in the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer. When this molar ratio is satisfied, the crosslinked polymer produced can have an appropriate ratio of first chains and second chains, and therefore can exhibit excellent hydroxide ion conductivity and mechanical properties.

[0054] The reaction in step (c) can be carried out at 40-60°C for 10-16 hours, preferably 45-55°C for 11-13 hours. If the polymerization reaction temperature is less than 40°C or the reaction time is less than 10 hours, the crosslinking reaction between polymers does not occur sufficiently, and the hydroxide ion conductivity and alkaline stability may decrease. Conversely, if the polymerization reaction temperature is more than 60°C or the reaction time is more than 16 hours, the crosslinking rate between polymers increases excessively, and the crosslinked polymer solution may gel.

[0055] Meanwhile, after the step (c), the method may further include a step (d) of reacting the crosslinked copolymer with trimethylamine in order to convert all the halogen groups remaining in the crosslinked copolymer into amine groups. The step (d) may be carried out, for example, at 40 to 60° C. for 10 to 30 hours, preferably at 45 to 55° C. for 20 to 30 hours.

[0056] As described above, in the present invention, a halogen functional group is introduced into the SEBS main chain and reacted with the PmTP main chain containing an amine group to produce a crosslinked copolymer, so that SEBS and PmTP can be quantitatively crosslinked without side reactions, and the degree of crosslinking can be easily controlled by adjusting the amount of each main chain.

[0057] Furthermore, according to the method, the crosslinked copolymer can be produced more easily and in a higher yield, thereby improving the productivity of the process and reducing costs.

[0058] The present invention will be described in more detail with reference to the following examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited thereto. EXAMPLES

[0059] [Example] <Material> Poly(styrene-b-ethylene-co-butylene-b-styrene) (SEBS, A1535H) with a styrene content of 57% was obtained from Clayton (Houston, TX, USA), m-terphenyl (99%) and triethylsilane (98%) were obtained from Alfa-Aesar (Haverhill, MA, USA). 6-Bromohexanoyl chloride (97%), aluminum chloride (99%) and N-methyl-4-piperidone (97%) were purchased from Sigma-Aldrich (St. Louis, MO, USA). Trifluoromethansulfonic acid (98%) was obtained from TCI (Tokyo, Japan). Trifluoroacetic acid was purchased from Daejung Chemical Metals (Siheung, Republic of Korea). All other chemicals were obtained from commercial sources.

[0060] <Confirmation of polymer chemical structure> The chemical structures of the polymers obtained at each step in the following examples are as follows: 1 It was confirmed by 1 H NMR spectroscopy and Fourier transform infrared (FTIR) spectroscopy. 1 H NMR spectra were obtained using a 400 MHz NMR instrument (Agilent 400MR) with CDCl3 as the solvent. FTIR spectra were obtained using a PerkinElmer Spectrum Two ATR-FTIR spectrometer. Spectra were obtained from 4000-400 cm -1 was collected up to now.

[0061] Example 1: Preparation of 30x-PmTP-SEBS (crosslinking degree 30%) membrane (1) Synthesis of poly(m-terphenyl N-methylpiperidine) 2 [ka] (In the above reaction formula, n is 158.)

[0062] In a completely dry 50 mL two-neck round bottom flask equipped with a magnetic stirrer, m-terphenyl (3.00 g, 13.03 mmol) and N-methyl-4-piperidone (1.92 g, 16.93 mmol) were poured under nitrogen atmosphere and then dissolved in dichloromethane (DCM, 15 mL). After the mixture was completely dissolved, the solution was cooled to 0° C. using an ice bath. Trifluoroacetic acid (TFA, 2.23 g, 19.54 mmol) and trifluoromethanesulfonic acid (TFSA, 19.56 g, 130.30 mmol) were slowly added while the solution was continuously stirred. The color of the solution changed from light brown to dark brown. After 48 hours, the viscous solution was poured into KOH solution (500 mL) and the precipitated polymer was filtered through filter paper and washed several times with deionized water to remove residual reactants. The resulting polymer was dried in a vacuum oven for 24 hours to give poly(m-terphenyl-N-methylpiperidine) as a white fibrous solid (4.13 g, 97.4%); δH (400 MHz, CDCl3), 7.79-7.27 (12H, broad signal, H 1-5 ), 7.75-7.38(8H, wide signal, H 6、7 ), 2.35-2.20 (3H,s,H8) (Figure 9).

[0063] (2) Synthesis of Bromohexyl-SEBS3 (2-1) Synthesis of bromohexanoyl SEBS4 [ka] (In the above reaction formula, the sum of q1, q2, q5, and q6 is 711, the sum of q3 and q4 is 996, and the ratio of the sum of q1 and q6 to the total sum of q1, q2, q5, and q6 is 0.3.)

[0064] In a 500 mL two-neck round bottom flask equipped with a magnetic stirrer, SEBS (5.00 g, 27.36 mmol) was poured into a nitrogen atmosphere and dissolved in dichloromethane (150 mL). After the polymer was completely dissolved, aluminum chloride (2.01 g, 15.06 mmol) and 6-bromohexanoyl chloride (3.21 g, 15.06 mmol) were slowly added to dichloromethane (50 mL). After 24 hours, the reaction mixture was poured into a large amount of ethanol (1000 mL) and the precipitated polymer was filtered through filter paper and washed several times with ethanol to remove residual reactants. The resulting polymer was dried in a dryer at room temperature (25°C) for 24 hours to obtain white rubber-like bromohexanoyl SEBS4 (8.20 g, 97.7%), in which 70 mol% of the total 100 mol% of styrene contained in SEBS had bromohexanoyl functional groups; δH (400 MHz, CDCl3) 7.92-7.39 (4H, broad signal, H 6、7 ), 7.25-6.29(10H, wide signal, H 8、9、10 ), 3.50-3.37(3H, wide signal, H1), 3.04-2.80(3H, wide signal, H5), 2.70-2.32(2H, wide signal, H 12 ), 2.02-0.55(46H, wide signal, H 2-4、11、13-18 ) (Figure 10(b)); ATR-FTIR (cm -1 ) 3026 (aromatic CH stretching), 2922-2852 (alkane CH stretching), 1680 (C=O stretching) (Figure 11).

[0065] (2-2) Synthesis of Bromohexyl SEBS3 [ka] (In the above reaction formula, the sum of q1, q2, q5, and q6 is 711, the sum of q3 and q4 is 996, and the ratio of the sum of q1 and q6 to the total sum of q1, q2, q5, and q6 is 0.3.)

[0066] Bromohexanoyl SEBS4 (8.00 g, 14.74 mmol) was dissolved in chloroform (200 mL) under nitrogen atmosphere in a 500 mL two-necked round bottom flask equipped with a magnetic stirrer connected to a reflux condenser. After the bromohexanoyl SEBS4 was completely dissolved, triethylsilane (23.55 mL, 147.4 mmol) and trifluoroacetic acid (22.56 mL, 294.8 mmol) were added. The reaction mixture was slowly heated to 105°C and maintained at this temperature for 48 hours. After the reaction mixture was cooled to room temperature, it was neutralized by adding 1M KOH (200 mL). The organic layer was poured into methanol (1000 mL) and the precipitated polymer was filtered through filter paper and washed several times with methanol to remove residual reactants. The resulting polymer was dried in a desiccator at room temperature for 24 hours to give white rubbery bromohexyl SEBS3 (7.66 g, 93.54%); δH (400 MHz, CDCl3) 7.23-6.19 (12H, broad signal, H 6-10 ), 3.51-3.38(3H, wide signal, H1), 2.67-2.26(5H, wide signal, H 5’、12 ), 2.11-0.55(47H, wide signal, H 2-5、11、13-18 ) (Figure 10(c)); ATR-FTIR (cm -1 ) 3024 (aromatic CH stretching), 2922-2852 (alkane CH stretching) (Figure 11).

[0067] (3) Preparation of crosslinked poly(m-terphenyl-N-methylpiperidinium)-SEBS (x-PmTP-SEBS) membrane [ka] (In the above reaction formula, n is 158, the sum of q1, q2, q5, and q6 is 711, the sum of q3 and q4 is 996, and the ratio of the sum of q1 and q6 to the total sum of q1, q2, q5, and q6 is 0.3.)

[0068] Poly(m-terphenyl N-methylpiperidine)2, bromohexyl SEBS3, and HPLC grade chloroform (20 mL) were placed in a 20 mL bottle and the mixture was stirred until the polymers were completely dissolved. Poly(m-terphenyl N-methylpiperidine)2 was used at a ratio of 30 mol% relative to bromohexyl SEBS3. The polymer solution was heated at 45 °C overnight to induce cross-linking. The polymer solution was cooled to room temperature, filtered, poured into a glass Petri dish, and dried at room temperature for 24 hours. The formed membrane was peeled off from the Petri dish and immersed in deionized water to wash out the remaining solvent. The membrane was then immersed in an aqueous trimethylamine (TMA) solution at 40 °C for 24 hours, followed by rinsing with deionized water (DI) to remove the TMA. The membrane was immersed in a 1 M KOH solution at room temperature for a minimum of 24 hours to induce cross-linking. - Ions and OH - Finally, the membrane was washed several times with DI before measurements were taken.

[0069] Example 2: Preparation of 40x-PmTP-SEBS (40% cross-linking degree) membrane A 40x-PBB-SEBS membrane was prepared in the same manner as in Example 1, except that in step (3), poly(m-terphenyl-N-methylpiperidine) 2 was used in an amount of 40 mol % relative to bromohexyl SEBS 3 .

[0070] Example 3: Preparation of 50x-PmTP-SEBS (50% cross-linking) membrane A 50x-PBB-SEBS membrane was prepared in the same manner as in Example 1, except that in step (3), poly(m-terphenyl-N-methylpiperidine) 2 was used in an amount of 50 mol % relative to bromohexyl SEBS 3 .

[0071] Flexible film-like membranes having thicknesses of 35 to 40 μm were obtained in Examples 1 to 3. Fig. 12 is a photograph of the membranes produced in Examples 1 to 3.

[0072] In addition, the FTIR spectra of 30x-PmTP-SEBS, 40x-PmTP-SEBS, and 50x-PmTP-SEBS in Examples 1 to 3 showed that the 3000-2800 cm -1 (Aliphatic CH) and 1600-1800cm -1 The (aromatic C=C) peak was observed to decrease, indicating that cross-linking was successful (Figure 13).

[0073] Experimental Example 1: Ion exchange capacity (IEC), water content (WU), swelling ratio (SR), density, and free volume (1) Measurement of ion exchange capacity (IEC) a. Experimental IEC The ion exchange capacity (IEC) of each membrane was measured using the back titration method. - The membranes in the form of 0.01M HCl standard solution were immersed for 24 hours. The residual HCl was again titrated with 0.01M NaOH standard solution using a phenolphthalein indicator. The membranes were weighed (W dry The experimental IEC (meq g -1 ) was calculated in moles of exchangeable hydroxide ions per gram: IEC(meq g -1 )=(C0V0-C0V x ) / W dry where V0 and V x are the volumes of NaOH before and after the titration, respectively, C0 is the molar concentration of NaOH used in the back titration, and W dry is the weight of the membrane after drying in an oven for a minimum of 12 hours.

[0074] b. Theoretical IEC The theoretical IEC value is: 1 The number of Br atoms contained in bromohexyl SEBS3 was determined based on the calculated H NMR spectrum and the masses of the two polymers (2 and 3) used in the cross-linking process.

[0075] (2) Water content (WU) and swelling ratio (SR) The water content (WU,%) and swelling ratio (SR,%) of each membrane were calculated by immersing the circular membrane in water at 20°C and 80°C. OH - The membrane was soaked in deionized water for a minimum of 24 hours, and then the membrane surface was wiped and weighed (W wet ) and thickness (T wet The membrane was dried in vacuum for 24 hours, and the weight of the dry membrane (W dry ) and thickness (T dry The moisture content (%) and swelling ratio (%) were calculated using the following formula: WU(%)=(W wet -W dry ) / W dry ×100 SR(%)=(L wet -L dry ) / L dry ×100 or (T wet -T dry ) / T dry ×100 The hydration number (λ) of each membrane was calculated from the WU and the experimental IEC of each membrane. The following equation was used to calculate the hydration number: Hydration number(λ)=(Water uptake(%)×1000) / (IEC×18)

[0076] (3) Density In step (3) of each Example, the Br2 was obtained after crosslinking of poly(m-terphenyl N-methylpiperidine)2 and bromohexyl SEBS3 and treatment with trimethylamine. - The density of the as-form membrane (i.e., the membrane before ion-exchange by KOH treatment) was measured in the following manner. Before the measurements, the membranes were dried in an oven at 40 °C for a minimum of 24 h and then resuspended in n-heptane (density = 0.684 g cm) at room temperature. -3 The density of each film was measured using the buoyancy method (g cm) using the following equation: -3 ) was calculated as follows: density(g cm -3 )=W air / (W air -W hep )×D hep Here, W air is the weight of the film in air, W hep is the weight of the membrane immersed in heptane, D hep is the density of n-heptane, 0.684 g cm -3 It is.

[0077] (4) Fractional Free Volume (FFV) Fractional free volume (FFV) is a dimensionless parameter that characterizes the volume of a cell that is not occupied by the polymer and can be calculated using the Visualizer module of the Material studio package. The molecular surface can be calculated in three ways, but in the present invention, the van der Waals (vdW) surface created by intersecting the surface with the vdW radii of the atoms was obtained. The following equation was used to determine the fractional free volume: FFV=(V sp -1.3V vdW ) / V sp Here, V vdW is the vdW volume calculated by the group contribution method, and 1.3 is the universal packing factor. V sp denotes the specific volume defined by the inverse density.

[0078] (5) Results The IEC, WU, SR, density, and FFV of the x-PmTP-SEBS membranes of Examples 1 to 3 are shown in Table 1.

[0079] [Table 1] a1 Theoretical IEC calculated based on H NMR spectrum b Experimental IEC measured by back titration

[0080] IEC is defined as the milliequivalent of ion-conducting groups per unit mass of the polymer electrolyte membrane. In general, the higher the IEC of a polymer electrolyte membrane, the more water it can contain. Water can act as a mediator for hydroxide ion conduction in anion exchange membranes (AEMs), so the higher the IEC, the higher the ionic conductivity. However, excessively high IEC sometimes leads to an increase in water content (WU), which reduces ionic conductivity through a mechanism called the "dilution effect." When this phenomenon occurs, the SR of the membrane also increases, reducing the mechanical properties of the membrane. Therefore, for an AEM to have high ionic conductivity and good mechanical properties, the IEC must be compatible.

[0081] The theoretical IECs of 30x-PmTP-SEBS, 40x-PmTP-SEBS and 50x-PmTP-SEBS were 1.90, 1.79 and 1.69 meq g, respectively. -1 The experimental IEC values ​​of x-PmTP-SEBS membranes were measured using the back titration method. The results showed that the experimental IEC values ​​were similar to the theoretical values ​​for all three membranes.

[0082] The WU and SR measurements of x-PmTP-SEBS membranes showed that WU and SR decreased with increasing crosslinking degree for all three membranes. Due to the inherent properties of SEBS as an elastomeric polymer, the WU and SR values ​​were higher when the crosslinking degree was low. With increasing crosslinking degree, the polymer chains form an increasingly dense network, resulting in a decrease in WU and SR values. This phenomenon is commonly observed in general crosslinked membranes. However, the x-PmTP-SEBS membranes showed intermediate levels of SR and higher WU (over 127%) compared to other SEBS-based crosslinked membranes.

[0083] Next, the density and FFV of the x-PmTP-SEBS membrane were measured. Generally, as the degree of crosslinking increases, the polymer density increases while the FFV decreases. However, the x-PmTP-SEBS membrane developed in the present invention showed the opposite trend (i.e., the polymer density decreased [30x-PmTP-SEBS (1.136)>40x-PmTP-SEBS (1.131)>50x-PmTP-SEBS (1.127)]), while the FFV increased with increasing degree of crosslinking. This behavior is due to the twisted structure of m-terphenyl that has entered the polymer backbone, which suppresses the packing of the polymer chains and at the same time contributes to the increase in FFV. This twisted shape is believed to be the cause of the high WU of the x-PmTP-SEBS membrane, since water can be effectively absorbed inside the twisted structure despite the crosslinked structure.

[0084] The calculation of the relative hydration number (λ) of the x-PmTP-SEBS membrane with respect to the IEC value showed that the x-PmTP-SEBS membrane is comparable to other SEBS-based crosslinked membranes (

[48] J. Membr. Sci. 599 (2020), 117829;

[50] Eur. Polym. J. 154 (2021), 110528;

[51] J. Polym. Sci. 58 (2020) 2181-2196;

[52] Int. J. Hydrogen Energy 46 (2021) 36301-36313;

[53] Int. J.Hydrogen Energy 45 (2020) 15658-15671), PP-based membranes ([3] Nat. Energy 4 (2019) 392-398; [4] Nat. Commun. 12 (2021) 2367; [6] Int. J. Hydrogen Energy 46 (2021) 18524-18533; [8] J. Mater. Chem. A. 9 (2021) 327-337;

[36] Energy Environ.Sci. 13 (2020) 3633-3645), and previously reported crosslinked PPO-SEBS membranes (

[54] J. Mater. Chem. A. 9 (2021) 1062-107] were confirmed to exhibit higher hydration numbers (30xPmTP-SEBS: 45.2, 40x-PmTP-SEBS: 42.2 and 50x-PmTP-SEBS: 42.0) (Figure 2a).

[0085] Experimental Example 2: Mechanical and Thermal Properties (1) Mechanical properties A bench-top tensile tester (Shimadzu E-TEST E2-L, Kyoto, Japan) was used to measure the tensile strength at 10 mm min at 25 °C and 50% relative humidity. -1 At a crosshead speed of - The mechanical properties of the membranes in the morphology were measured. The initial sample cross-sectional area was used to determine the engineering stress. The initial slope of the stress-deformation curve was used to calculate Young's modulus. For this test, each membrane sample was prepared in a dumbbell shape with a total area of ​​40 mmХ10 mm and a test area of ​​20 mm.

[0086] (2) Thermal stability The thermal stability of the films was investigated by thermogravimetric analysis (TGA) using a Scinco TGA N-1000 instrument (Seoul, Korea). TGA was performed at 30–800 °C for 10 °C min under nitrogen atmosphere. -1 It operated at a heating rate of . The glass transition temperature (TG) of each film was measured by differential scanning calorimetry (DSC) using a PerkinElmer DSC4000 (Waltham, Ma, USA). Samples were prepared in aluminum pans and heated and cooled at rates of 10 °C min−1. -1 The temperature was measured from -40 to 200 °C for two cycles. The Tg was determined in the second heating cycle.

[0087] (3) Results When used in AEMFC, AEM not only acts as an electrolyte to conduct hydroxide ions, but also as a separator between the positive and negative electrodes to prevent H2 and O2 fuel from migrating from one electrode to the other. Therefore, the mechanical and thermal stability of the membrane are also important factors to consider for the commercialization of AEMFC.

[0088] The mechanical properties of x-PmTP-SEBS membranes were investigated based on the stress-strain curves (Figure 14 and Table 2). As expected, the stress (tensile strength) and Young's modulus of the thin films increased with increasing crosslinking degree: 30xPmTP-SEBS (15.3 MPa and 91.4 MPa) < 40xPmTP-SEBS (18.9 MPa and 99.7 MPa) < 50xPmTP-SEBS (28.5 MPa and 170.3 MPa). These results confirmed that the crosslinking process contributed to the improvement of the mechanical properties of the membranes. This improvement was due to the fact that the proportion of SEBS as an elastomeric polymer was decreased with increasing crosslinking degree, while at the same time increasing the relative proportion of poly(m-terphenyl-N-methylpiperidine) units as a rigid polymer.

[0089] [Table 2]

[0090] The mechanical properties of x-PmTP-SEBS membranes were also compared with those of other SEBS-based AEMs and PP-based AEMs (

[54] J. Mater. Chem. A. 9 (2021) 1062-1079;

[51] J. Polym. Sci. 58 (2020) 2181-2196;

[52] Int. J. Hydrogen Energy 46 (2021) 36301-36313;

[47] J. Membr. Sci. 643 (2022), 120029;

[53] Int. J.Hydrogen Energy 45 (2020) 15658-15671;

[38] J. Power Sources 480 (2020), 228805; [3] Nat. Energy 4 (2019) 392-398;

[34] ACS Macro Lett. 6 (2017) 566-570; [8] J. Mater. Chem. A. 9 (2021)327-337; [4] Nat. Commun. 12 (2021) 2367;

[61] Membranes 10 (2020) 1-16;

[62] J. Membr. Sci. 598 (2020)) (Table 2 and Figure 2b). The results showed that the membranes in which SEBS was crosslinked with the rigid polymer showed higher tensile strength and Young's modulus (i.e., improved mechanical properties) than the membranes in which SEBS or only the SEBS component was crosslinked. Furthermore, the x-PmTP-SEBS membranes crosslinked with SEBS showed much higher tensile properties (deformation values) than the PP-based membranes containing poly(terphenyl) and poly(biphenyl). These results strongly suggest that the mechanical properties of the membrane can be controlled by crosslinking two polymers with different properties, as proposed in this invention.In addition, the x-PmTP-SEBS membrane showed a higher deformation rate than the previously developed crosslinked PPO-SEBS membrane, which is believed to be due to the plasticizer effect caused by the membrane absorbing more water in the free volume induced by the m-terphenyl structure.

[0091] Next, the thermal stability of x-PmTP-SEBS membranes was determined using TGA and DSC. In the TGA results, the thermal decomposition process proceeded in three stages (Figure 15). The first weight loss observed in the temperature range below 100 °C was attributed to the evaporation of water contained in the membrane. The amount of water inside the membrane decreased with increasing crosslinking degree, which was consistent with the WU results. The second weight loss occurred around 200 °C and was attributed to the decomposition of conductive head groups, followed by the decomposition of polymer backbone chains finally around 400 °C.

[0092] Analysis of the DTG graph showed two peaks at 190°C and 250°C, which correspond to the decomposition of the quaternary ammonium (QA) group and the crosslinked piperidinium, respectively (Figure 15a). In general, QA groups exhibit higher thermal stability, i.e., higher degradation temperatures, when introduced into crosslinked structures compared to non-crosslinked structures. The observed values ​​of the present invention are consistent with this trend. In addition, in the DTG graph, the peak intensity at 190°C, which corresponds to the decomposition of the QA group, tended to decrease with increasing crosslinking degree, while the peak intensity at 250°C, which corresponds to the decomposition of the crosslinked piperidinium, tended to increase. These results confirmed that the amount of QA in the film decreased and the amount of crosslinked piperidinium increased with increasing crosslinking degree. The third weight loss, which began at about 400°C, was due to the decomposition of the polymer backbone.

[0093] Next, we tried to determine the glass transition temperature (Tg) of each polymer. In the x-PmTP-SEBS film, no peak was observed at temperatures up to 200°C, where the conductive head group began to decompose (Figure 15b). The Tg of general SEBS is about 46°C, but no Tg peak was observed in x-PmTP-SEBS until the temperature reached the decomposition temperature of ammonium from 180°C. This result indicates that the introduction of rigid poly(m-terphenyl-N-methylpiperidine) units combined with a cross-linked structure effectively improves the alignment between the polymer components and increases the thermal stability of SEBS as a rubbery polymer.

[0094] These TGA and DSC results indicated that the x-PmTP-SEBS membrane crosslinked with poly(m-terphenyl N-methylpiperidine) 2 and bromohexyl SEBS 3 exhibited high thermal stability suitable for the operation of fuel cells.

[0095] Experimental Example 3: Morphological analysis (1)Measurement method The surface morphology of each membrane was analyzed using Pt-coated scanning electron microscope (SEM, JSM-7800F, Tokyo, Japan) images at an accelerating voltage of 15.0 kV. The microphase separation of the membranes was observed using an atomic force microscope (AFM, Bruker MUMTIMODE-8-AM, Billerica, MA, USA). A high-resolution X-ray diffractometer (HR-XRD, SmartLab, Rigaku, Japan) was used to measure the surface morphology of the membranes using Cu-Kα X-rays (λ = 1.54 Å) in the 2θ range from 0° to 5° at 0.2° min -1 A scanning speed of 100 s was used to collect small angle X-ray diffraction scattering spectra of the membranes. The membranes were thoroughly dried at 40 °C before the measurements.

[0096] (2) Results The phase separation present in each membrane was confirmed by SEM. The images showed that the phase separation was more obvious in 50-PmTP-SEBS, which has a higher crosslinking degree than 30-PmTP-SEBS (Figures 3a-3c). The reason why the phase separation becomes more obvious as the crosslinking degree increases is because the alignment of the polymer structure is affected by the crosslinking degree. More specifically, when the crosslinking degree is low, SEBS remains randomly crosslinked with poly(m-terphenyl N-methylpiperidine), and such a structure makes it difficult for the SEBS components, which are very vulnerable to phase separation, to align well, leading to a limited level of phase separation. However, with an increase in the crosslinking degree, the bromohexyl SEBS becomes increasingly crosslinked with poly(m-terphenyl N-methylpiperidine) to improve the alignment of the polymer chains.

[0097] AFM images of x-PmTP-SEBS membranes further confirmed phase separation by the coexistence of dark hydrophilic and light hydrophobic regions, and ion clusters increased in size with increasing cross-linking degree (Figures 3d-3f) due to increased phase separation.

[0098] SAXS analysis further confirmed that the q value decreased (i.e., the d-spacing increased) with increasing crosslinking degree (Figure 4). This decrease occurred because increasing the crosslinking degree promoted the aggregation of conductive groups and promoted phase separation between hydrophilic and hydrophobic units, which increased the size of ion clusters. This result was consistent with the SEM and AFM results.

[0099] Experimental Example 4: Moisture retention capacity (1)Measurement method The freezing and non-freezing water content of the membranes was measured in the fully hydrated state by DSC using a PerkinElmer DSC4000. A fully hydrated membrane sample was sealed in an aluminum pan and a sealed empty aluminum pan was also prepared for use as a reference. Both pans were weighed and frozen at -40 °C inside the DSC chamber. The temperature was then held constant while the system equilibrated. The DSC chamber was then cooled to -40 °C for 2 °C min -1 The film was heated to 20 °C at a heating rate of 100 Hz. This cycle was repeated twice and the value was calculated for the second heating cycle. The amount of frozen water in each film was calculated by the area of ​​the melting heat resistance peak (ΔH m ) was calculated by integrating the WU (%) of the membrane. The WU (%) of the membrane was used to determine the total water content. The frozen and non-frozen water contents were calculated using the following formula: Freezing water(%)=[melting enthalpy(J g -1 )] / [melting endothermic heat of funsion of pure water(334J g -1 )] x 100 Non-freezing water(%)=total water(%)-freezing water(%)

[0100] (2) Results In AEMFC, water plays the role of a medium to conduct hydroxide ions formed at the positive electrode to the negative electrode. Therefore, the water capacity of AEM is important to characterize the ion conducting ability. Water in the membrane is generally divided into free water and bound water. Free water does not actively interact with the ion conducting head group, and its freezing point and boiling point temperature are similar to those of ordinary water. Conversely, bound water has a stronger interaction with the ion conducting head group, and therefore exhibits a lower freezing point and a higher boiling point than free water. In previous studies, the content of bound water had a greater effect on the ionic conductivity of AEM than free water. Considering that fuel cells generally operate at 90%-95% RH than water, i.e., 90%-95% hydrated H2 and O2, increasing the content of bound water should improve the overall cell performance.

[0101] The water content of x-PmTP-SEBS membranes was measured using TGA and DSC. In the TGA results, the weight loss observed below 100 °C was assumed to correspond to the evaporation of free water, whereas the weight loss above 100 °C and 150 °C was assumed to be due to the evaporation of bound water (Figure 5a). This TGA-based water analysis method allows only qualitative, not quantitative, analysis due to the variable WU for each tested membrane. Therefore, the results obtained with this approach were only used to determine how the free and bound water contents differ from each other.

[0102] With increasing cross-linking degree, the overall WU of x-PmTP-SEBS membranes decreased, but the bound water content increased (Figure 5b). This is because the content of poly(m-terphenyl N-methylpiperidine) increased with increasing cross-linking degree. More specifically, the twisted structure of m-terphenyl units in poly(p-terphenyl N-methylpiperidine) enhanced the interaction with water by increasing the FFV of each membrane. This result was consistent with the FFV analysis results (Table 1).

[0103] The state of water was additionally analyzed using DSC to examine the content of “unfrozen water” and “frozen water” (frozen-free water and frozen-bound water). The following peaks were observed in all three x-PmTP-SEBS membranes: T F1 and T, which corresponds to the freezing temperature of the frozen bound water. F2 (Dotted line in Figure 16). In the case of non-frozen water, no phase change was observed because this form of water strongly interacts with the ion-conducting head groups. On the other hand, the peaks corresponding to free water and frozen-bound water partially overlapped, and these two types of water were treated as frozen water. Based on this result, the DSC enthalpy of fusion (ΔH m ) was calculated to determine the ratio of frozen water to non-frozen water relative to the total water for each membrane (Table 3). As expected, the ratio of non-frozen water increased with increasing crosslinking degree. This is because the interaction between the ion-conducting headgroups and water was strengthened with increasing crosslinking degree.

[0104] [Table 3]

[0105] To confirm this interpretation, F2 Further analysis was performed on T F2 shifted to lower temperatures with increasing degree of crosslinking (i.e., the interaction between the ion-conducting head group and water became stronger). This was consistent with the TGA results, confirming that the introduction of crosslinking bonds increased the bound water content. These results confirmed that the introduction of poly(m-terphenyl N-methylpiperidine) units could successfully increase the bound water content by improving the free volume, as in the previously crosslinked PPO-SEBS containing triazole groups, without the use of triazole groups.

[0106] Experimental Example 5: Hydroxide ion conductivity (1)Measurement method The hydroxide ion conductivity (σ) of each membrane was measured by four-probe impedance spectroscopy using an AC impedance analyzer (SP-200, Bio-Logic SAS, Claix, France). The electrode system was coupled at frequencies ranging from 100 mHz to 2 MHz. Rectangular samples were prepared with dimensions of 1x4 cm. The hydroxide ion conductivity was measured using a resistor (R) in deionized water at 20 °C to 80 °C. The hydroxide ion conductivity was calculated using the following equation: σ=L / (R×A) where L is the distance between the reference electrodes and A is the cross-sectional area of ​​the membrane.

[0107] (2) Results In AEMFC, the AEM conducts hydroxide ions and generates energy. Therefore, the hydroxide ion conductivity of the AEM is one of the most important properties that determine the performance of a single cell. In this study, the hydroxide ion conductivity of x-PmTP-SEBS AEMs was measured at 20-80 °C (Figure 6 and Table 4). The results showed that the ionic conductivity of each membrane increased with increasing crosslinking degree over the entire temperature range (Figure 6a).

[0108] To eliminate the effect of the IEC difference of each membrane on the ionic conductivity, the normalized conductivity was measured and compared. Such results also showed that the ionic conductivity increased with increasing crosslinking degree (Figure 6b). In particular, 50xPmTP-SEBS showed the highest ionic conductivity (56.31 mS / cm at 20 °C and 116.32 mS / cm at 80 °C) among the three membranes, despite its high level of crosslinking and low IEC and WU. This is because the crosslinking degree increased, allowing the membrane to well establish a phase-separated morphology while increasing the size of ion clusters and the ratio of bound water, as confirmed by the morphological analysis results using conventional AFM, SEM, and XRD, and the water-holding capacity measurements using TGA and DSC.

[0109] The normalized conductivity of the x-PmTP-SEBS membranes was compared with that of various AEMs, including the previously developed and commercialized cross-linked PPO-SEBS AEM ([3] Nat. Energy 4 (2019) 392-398; [4] Nat. Commun. 12 (2021) 2367; [5] Adv. Funct. Mater. 28 (2018) 1-10; [6] Int. J. Hydrogen Energy 46 (2021) 18524-18533; [8] J. Mater. Chem. A. 9 (2021) 327-337; [9] J. Membr. Sci. 642 (2022), 119966;

[36] Energy Environ.Sci. 13 (2020) 3633-3645;

[37] J. Power Sources 487 (2021), 229429;

[49] J. Membr. Sci. 644 (2022), 120109;

[61] Membranes 10 (2020) 1-16) were additionally compared (Figure 6b). The x-PmTP-SEBS membrane showed high ionic conductivity despite the low IEC value. This confirmed that the cross-linking of poly(m-terphenyl N-methylpiperidine) with bromohexyl SEBS provides such x-PmTP-SEBS membrane with a very high level of ionic conduction efficiency for two reasons. The first is the good phase separation effect originated from SEBS, a triple block copolymer, confirmed by morphological analysis. The second reason is that the twisted structure of poly(m-terphenyl N-methylpiperidine) enhanced the interaction between the ion-conducting head group and water, as confirmed by bound water analysis using TGA and DSC.

[0110] The normalized conductivity of the crosslinked x-PmTP-SEBS membrane is much higher than that of the crosslinked x-TQA-PPO-SEBS prepared by crosslinking PPO and SEBS via triazole reported previously. This result suggests that the introduction of the twisted poly(m-terphenyl-N-methylpiperidine) structure to increase the bound water content was more effective than the introduction of the hydrogen-bonding sites of triazole. Due to such combined effects, the 50xPmTP-SEBS had a normalized conductivity of 33.52 mS cm at 20 °C. -1 It showed an excellent normalized conductivity of .

[0111] The ionic conductivity of the crosslinked x-PmTP-SEBS membrane was additionally measured at 95% room humidity (RH) and 60°C, which are the operating conditions of fuel cells in practical applications. The ionic conductivity of water (50xPmTP-SEBS: 32.44 mS cm -1 >40x-PmTP-SEBS: 30.73mS cm -1 >30x-PmTP-SEBS: 28.58mS cm -1 ), the RH conductivity increased with increasing crosslinking degree (Table 4). This is because the amount of twisted m-terphenyl units in the crosslinked x-PmTP-SEBS was increased, as confirmed by the aqueous state analysis, and the highly crosslinked membranes had higher conductivity even under RH conditions.

[0112] [Table 4] a Measured at 95% RH and 60°C

[0113] Experimental Example 6: Alkaline Stability (1)Measurement method OH -Chemical stability was assessed by measuring the change in IEC and conductivity upon immersion of the morphological membranes in 2M KOH solution at 80°C for 600 hours. Prior to measurement, each membrane was immersed in freshly prepared 1M KOH solution at room temperature for a minimum of 24 hours. After this period, the hydroxide ion conductivity of each membrane was measured in deionized water at 20°C (at 120 hour intervals) and the IEC was measured before and after each alkaline stability test using the back titration method described above.

[0114] (2) Results The alkaline stability test results of the x-PmTP-SEBS membrane are shown in FIG. All three membranes with different crosslinking degrees showed excellent alkaline stability (conductivity and IEC retention rate were 99% or more for 600 hours). It was also found that the alkaline stability was further improved with an increase in the crosslinking degree. The high alkaline stability of the x-PmTP-SEBS membrane was due to the fact that the two polymers constituting the x-PmTP-SEBS membrane (poly(m-terphenyl N-methylpiperidine) and SEBS) were all polymers without aryl ether bonds, which are highly resistant to backbone decomposition induced by hydroxide ions. The crosslinking of these two polymers also improved the chemical stability of the ion-conducting group. As confirmed by the previous water retention capacity measurement, the content of bound water increased with an increase in the crosslinking degree, and this bound water surrounded the ion conductor, creating a shielding effect and protecting it from the attack of hydroxide ions. The combination of all these factors improved the alkaline stability of this membrane.

[0115] In addition, the alkaline stability of the x-PmTP-SEBS membrane developed in the present invention was compared with that of some representative AEMs reported in the literature, including the previously developed crosslinked PPO-SEBS (xTQA50-PPO-SEBS,

[54] J. Mater. Chem. A. 9 (2021) 1062-1079) (

[47] J. Membr. Sci. 643 (2022), 120029;

[53] Int. J.Hydrogen Energy 45 (2020) 15658-15671;

[66] Macromolecules 52 (2019) 2139-2147;

[52] Int. J. Hydrogen Energy 46 (2021) 36301-36313;

[48] J. Membr. Sci. 599 (2020), 117829;

[50] Eur. Polym. J. 154 (2021), 110528;

[55] J. Membr. Sci. 633 (2021), 119418; [6] Int. J. Hydrogen Energy 46 (2021) 18524-18533;

[61] Membranes 10 (2020) 1-16; [8] J. Mater. Chem. A. 9 (2021) 327-337; [4] Nat. Commun. 12 (2021) 2367;

[49] J. Membr. Sci. 644 (2022), 120109; [3] Nat. Energy 4 (2019) 392-398; [9] J. Membr. Sci. 642 (2022), 119966;

[37] J. Power Sources 487 (2021), 229429;

[46] Angew. Chem. Int. Ed. 61(2022) 1-8;

[62] J. Membr. Sci. 598 (2020)) were additionally compared (Table 5). All x-PmTP-SEBS membranes showed higher residual conductivity values ​​(i.e., higher stability) than PP- and SEBS-based AEMs.

[0116] [Table 5A] [Table 5B] a QA=quaternary ammonium, Pip=piperidinium

[0117] Experimental Example 7: Preparation of membrane electrode assembly (MEA) and single cell measurement (1)Measurement method The single cell test was carried out as follows: First, the catalyst ink was added at 0.3 mg cm for the positive electrode. -2 For the negative electrode with Pt / C (46.2 wt%, Tanaka Kikinzoku Kogyo-TKK, Tokyo, Japan) and deionized water, 2-propanol, and 10 wt% FAA-3 ionomer solution, 0.4 mg cm of PtRu / C (HiSpec10000, Johnson Matthe, London) -2 The catalyst ink was then coated on the prepared membrane surface using an air spray gun, and then immersed in 1M KOH solution for 3 h to produce a catalyst-coated membrane (CCM). The CCM was used to fabricate a 5 cm2 membrane electrode assembly (MEA). 2 The electrodes were sandwiched between a 39BB gas diffusion layer (GDL, Sigracet, SGL Carbon, Wiesbaden, Germany) with an effective electrode area of ​​0.01 mm and a Teflon gasket. H2 and O2 were supplied at 0.6 L min -1 and 0.8L min -1 The fuel cell test was carried out at 60°C under RH95%. The polarization curves were then plotted at 50mA s -1 The measurements were performed at a scan speed of .

[0118] (2) Results The x-PmTP-SEBS membrane developed in this study exhibited excellent physicochemical stability, well-established phase separation morphology, and high conductivity in water and practical RH conditions. Single-cell tests were then carried out with the x-PmTP-SEBS membrane at 60°C and 95% RH.

[0119] The results showed that the maximum power density and current density (at 0.6 V) of such membranes increased with increasing crosslinking degree: 50xPmTP-SEBS (592 mW cm -2 and 1156mA cm -2 )>40x-PmTP-SEBS(496mW cm -2 and 926mA cm -2 )>30x-PmTP-SEBS(391mW cm -2 and 737mA cm -2 ) (Figure 8a). This result was consistent with the trends observed in the conductivity measurements (both in water and under real RH conditions).

[0120] For the 50xPmTP-SEBS membrane with the best cell performance, additional tests were performed at a back pressure of 0.1 MPa. As a result, a slightly improved cell performance was achieved: 50xPmTP-SEBS (642 mW cm -2 and 1315mA cm -2 ) (Figure 8b). This suggests that the cell performance can be further optimized.

[0121] The cell performance of 50xPmTP-SEBS membranes was reported in previous studies, and is comparable to that of other SEBS-based AEMs (

[47] J. Membr. Sci. 643 (2022), 120029;

[48] J. Membr. Sci. 599 (2020), 117829;

[51] J. Polym. Sci. 58 (2020) 2181-2196;

[53] Int. J.Hydrogen Energy 45 (2020) 15658-15671;

[66] Macromolecules 52 (2019) 2139-2147) or PP-based AEMs ([3] Nat. Energy 4 (2019) 392-398; [6] Int. J. Hydrogen Energy 46 (2021) 18524-18533; [8] J. Mater. Chem. A. 9 (2021) 327-337;

[34] ACS Macro Lett. 6 (2017) 566-570;

[67] J. Membr. Sci. 588 (2019), 117120;

[68] Int. J. Hydrogen Energy 44 (2019) 24954-24964) (Figure 17). Single-cell operation involves a variety of factors such as flow rate, back pressure, RH conditions, cell operating temperature, catalyst, and ionomer, making it difficult to directly compare cell performance measured at other conditions. However, the 50xPmTP-SEBS membrane, in which poly(m-terphenyl N-methylpiperidine) and bromohexyl SEBS were cross-linked with each other, showed a relatively high peak power density, even though it was measured at a relatively low H2 / O2 flow rate (0.6 / 0.8 L / min, respectively) and low temperature (60°C). These results indicate that due to the phase-separated morphology and high water retention capacity of x-PmTP-SEBS AEM, such membranes can provide high hydroxide ion conductivity and excellent cell performance when actually used in fuel cells.

[0122] conclusion The poly(m-terphenyl-N-methylpiperidinium)-SEBS membrane (x-PmTP-SEBS) according to one embodiment of the present invention exhibited higher tensile strength (15 MPa or more) and Young's modulus (91 MPa or more) than existing crosslinked SEBS membranes. In addition, the x-PmTP-SEBS membrane exhibited much higher elongation properties (118% or more at break) than general PP-based membranes.

[0123] And, the x-PmTP-SEBS membrane showed high dimensional stability at an SR of about 30%, despite its high WU (127% or more at 20° C.).

[0124] In addition, the x-PmTP-SEBS membrane according to one embodiment of the present invention exhibited high water retention capacity and high hydration number (λ>42) due to the well-segregated morphology originating from the triple block structure of SEBS and the free volume induced by the twisted structure of m-terphenyl. As a result, these membranes showed excellent normalized conductivity and excellent cell performance. In particular, the 50xPmTP-SEBS membrane with a crosslinking degree of 50% showed an IEC of 1.68 meq g -1 However, at 80°C in water, it was 116 mS cm -1 , 95% RH, 32 mS cm at 60°C -1 It exhibits high conductivity of 642 mW cm of H2 / O2 gas flow at 60 °C and 95% RH. -2 A high peak power density of

[0125] Moreover, all cross-linked x-PmTP-SEBS membranes based on polymer backbones lacking aryl-ether bonds exhibited excellent alkaline stability (more than 99% of ionic conductivity and IEC were maintained even at 80 °C and 2 M KOH for 600 h) and outperformed typical AEMs reported in the literature due to the shielding effect resulting from their high hydration numbers.

[0126] From the above results, it was confirmed that the polymer membrane including the cross-linked copolymer according to the embodiment of the present invention has excellent mechanical properties and excellent physicochemical and electrical properties. In addition, it was confirmed that the physical properties of the polymer membrane including the cross-linked copolymer can be controlled by adjusting the cross-linking degree of the cross-linked copolymer.

[0127] In addition, it was confirmed that the polymer membrane exhibits stable and excellent electrochemical properties, such as excellent ionic conductivity while having an appropriate IEC. These results show that the strategy used in the present invention can be used to develop an AEM with excellent performance, instead of a strategy to increase the IEC of the polymer.

Claims

1. A crosslinked copolymer comprising a first chain represented by the following chemical formula 1 and a second chain represented by the following chemical formula 2, the first chain and the second chain being crosslinked with each other: 【Chemistry 1】 In the above Chemical Formula 1, * indicates the bonding position with Chemical Formula 2. q 1 , q 2 , q 5 , and q 6 is an integer from 100 to 1,000, q 3 and q 4 is an integer from 150 to 2,000, a and b are each independently an integer from 3 to 10; R 1 ~R 4 are each independently hydrogen or -(CH 2 ) p -CH 3 and p is an integer from 0 to 5; 【Chemistry 2】 In the above Chemical Formula 2, * indicates the bonding position with Chemical Formula 1. R 5 is -(CH 2 ) p’ -CH 3 and p' is an integer from 0 to 5; n is an integer from 10 to 1,000.

2. The crosslinked copolymer according to claim 1, comprising 10 to 70 moles of the second chain per 100 moles of the first chain.

3. q 1 ~q 6 The crosslinked copolymer according to claim 1, wherein each of is independently an integer of 10 to 500.

4. q 1 ~q 6 q for the sum of 1 , q 2 , q 5 , and q 6 The crosslinked copolymer according to claim 1, wherein the ratio of the sum of is 0.2 to 0.

5.

5. q 1 , q 2 , q 5 , and q 6 q for the sum of 1 and q 6 The crosslinked copolymer according to claim 1, wherein the ratio of the sum of is 0.2 to 0.

5.

6. 2. The crosslinked copolymer according to claim 1, wherein a and b are each independently an integer of 4 to 6.

7. The cross-linked copolymer of claim 1 , which is represented by the following chemical formula 3: 【Chemistry 3】 In the above Chemical Formula 3, q 1 ~q 6 , a, b, and n are as defined in Formula 1 and Formula 2.

8. A polymer membrane comprising the crosslinked copolymer according to any one of claims 1 to 7.

9. The polymer membrane of claim 8 , wherein the polymer membrane is an anion exchange membrane.

10. (a) preparing a poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer represented by the following formula 1-1: (b) preparing a poly(m-terphenyl N-alkylpiperidine) polymer represented by the following formula 2-1: (c) crosslinking the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer with the poly(m-terphenyl-N-methylpiperidine) polymer to prepare a crosslinked copolymer; A method for producing a crosslinked copolymer comprising: 【Chemistry 4】 In the above Chemical Formula 1-1, q 1 , q 2 , q 5 , and q 6 is an integer from 100 to 1,000, q 3 and q 4 is an integer from 150 to 2,000, a and b are each independently an integer from 3 to 10; R 1 ~R 4 are each independently hydrogen or -(CH 2 ) p -CH 3 and p is an integer from 0 to 5; X 1 and X 2 are each independently a halogen group; 【Chemistry 5】 In the above Chemical Formula 2-1, R 5 is -(CH 2 ) p’ -CH 3 and p' is an integer from 0 to 5; n is an integer from 10 to 1,000.

11. The method of claim 10, further comprising the step of: (d) reacting the crosslinked copolymer with trimethylamine.

12. The method for producing a crosslinked copolymer according to claim 10, wherein the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer contains 30 to 90 moles of halogen groups per 100 moles of styrene repeating units.

13. 11. The method of claim 10, wherein in step (c), 10 to 70 moles of the poly(m-terphenyl N-alkylpiperidine) polymer is used per 100 moles of halogen groups contained in the poly(styrene-b-ethylene-co-butylene-b-styrene)-based polymer.

Citation Information

Patent Citations

  • Partially fluorinated anion exchange membrane and manufacturing method for thereof

    KR101535062B1